Social isolation during puberty affects female sexual behavior in mice - Kercmar, Jasmina; Tobet, Stuart A.; Majdic, Gregor (Frontiers in Behavioral Neuroscience, 2014)
Exposure to stress during puberty can lead to long-term behavioral alterations in adult rodents coincident with sex steroid hormone-dependent brain remodeling and reorganization. Social isolation is a stress for social animals like mice, but little is known about the effects of such stress during adolescence on later reproductive behaviors. The present study examined sexual behavior of ovariectomized, estradiol and progesterone primed female mice that were individually housed from 25 days of age until testing at approximately 95 days, or individually housed from day 25 until day 60 (during puberty), followed by housing in social groups. Mice in these isolated groups were compared to females that were group housed throughout the experiment. Receptive sexual behaviors of females and behaviors of stimulus males were recorded. Females housed in social groups displayed greater levels of receptive behaviors in comparison to both socially isolated groups. Namely, social females had higher lordosis quotients and more often displayed stronger lordosis postures in comparison to isolated females. No differences between female groups were observed in stimulus male sexual behavior suggesting that female ’attractiveness’ was not affected by their social isolation. Females housed in social groups had fewer cells containing immunoreactive estrogen receptor (ER) α in the anteroventral periventricular nucleus (AVPV) and in the ventromedial nucleus of the hypothalamus (VMH) than both isolated groups. These results suggest that isolation during adolescence affects female sexual behavior and re-socialization for one month in adulthood is insufficient to rescue lordosis behavior from the effects of social isolation during the pubertal period.